Three Writers of Arabic Texts in Yogyakarta - Muhamad Murtadlo (Center for Research and Development of Religious Literature and Heritage, 2014)
This study examines the use of the Arabic alphabet in religious literature in Yogyakarta. This study uses a case study on three figure writers of religious texts that using the Arabic alphabet in southern part of Central Java (Yogyakarta), namely Asrori Ahmad (Magelang), Ali Maksum (Yogyakarta), and Ahmad Mujab Mahalli (Bantul). This study concluded that the writing of religious texts in Arabic alphabet in the southern Java area had been carried out by means of using Arabic Pegon, and only a few people who wrote in the Arabic language. The transmission of Arabic Pegon in Yogyakarta is allegedly from north coast of Java, especially from Lasem / East Java. The tradition of Arabic language teaching in the pesantrens still focuses mostly on the reading effort, communication, and understanding and it is not oriented to the writing skill. The presence of international journals initiated by the College of Islamic religious institutions and the effort of translation business into Arabic from certain institutions gives an opportunity to strengthen the use of the Arabic alphabet in Indonesia.